2017
DOI: 10.1038/srep43464
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cell status monitors the treatment responses in breast cancer patients: a meta-analysis

Abstract: Whether circulating tumor cells (CTCs) can be used as an indicator of treatment response in breast cancer (BC) needs to be clarified. We addressed this issue by a meta-analysis. PubMed, EMBase and Cochrane library databases were searched in June 2016. Effect measures were estimated as pooled risk ratio (RR), odds ratio (OR) or mean difference by fixed- or random-effect models, according to heterogeneity of included studies. In total, 50 studies with 6712 patients were recruited. Overall analysis showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 59 publications
6
75
1
Order By: Relevance
“…Fifty‐two percent of the patients with increased CTCs at baseline changed to nonincreased CTCs at cycle 2 (21 days later). Likewise, in the SWOG S0500 study, 57% (165 out of 288) of those ABC patients with increased CTCs at baseline showed reduced CTC count below 5 after 21 days of treatment. Patients were on first line chemotherapy in the SWOG S0500 study and still the percentage of patients with decreased CTCs is similar to ours, which suggests similar treatment efficacy, since CTC level is a surrogate marker for the evaluation of minimal residual disease and for disease activity in breast cancer .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Fifty‐two percent of the patients with increased CTCs at baseline changed to nonincreased CTCs at cycle 2 (21 days later). Likewise, in the SWOG S0500 study, 57% (165 out of 288) of those ABC patients with increased CTCs at baseline showed reduced CTC count below 5 after 21 days of treatment. Patients were on first line chemotherapy in the SWOG S0500 study and still the percentage of patients with decreased CTCs is similar to ours, which suggests similar treatment efficacy, since CTC level is a surrogate marker for the evaluation of minimal residual disease and for disease activity in breast cancer .…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, CTC status can serve as an indicator to monitor the effectiveness of treatment, and thus, the CTC reduction observed may reflect the effectiveness of eribulin. Cox analysis showed that the higher the level of CTCs, the higher risk of death, in agreement with the results of Hayes et al, concluding that detection of elevated CTCs at any time during therapy is an accurate indication of subsequent rapid disease progression and mortality in metastatic breast cancer patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of this study showed that CytoSorter ® system can successfully isolate CTCs in BC patients with a better sensitivity and specificity, and CTCs can be used as a tool to assist in cancer screening and early diagnosis. Studies have shown CTCs could be used as a prognostic factor and a monitoring aid for recurrence in BC as well . Thus, more studies on larger patient population with follow‐up should be conducted to elucidate the clinical value of CTCs as a diagnostic, therapeutic, and prognostic indicator in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MBC usually have more CTCs and BC patients with more CTCs usually have shorter PFS and OS . Moreover, CTCs can be used as a monitoring tool to evaluate patients' response to the treatment and to see whether tumor recurrence occurs …”
Section: Introductionmentioning
confidence: 99%